Water quality characteristics and pollution levels of heavy metals in Lake Haiq, Ethiopia - Teklay, Aregawi; Amare, Meareg (Ethiopian Journal of Science and Technology, 2025)
The main aim of this study was to assess the level of water quality of Lake Haiq, Ethiopia with respect to selected physical parameters and heavy metals. Parameters such as temperature, pH, turbidity, electrical conductivity and total dissolved solids were measured in situ. While total alkalinity, chloride, ammonia, nitrate and sulphate were investigated using standard analytical procedures. the level of the studied heavy metals (Pb, Cd, Cu and Zn) was determined using the inductively coupled plasma-optical emission spectrometry. Sulphate, nitrate, ammonia, chloride, and total dissolved solids were within the recommended levels for a drinking water by the WHO guidelines. In contrast, the total alkalinity, turbidity and pH values were above the recommended limits, indicating the inconveniency to use the water for drinking. While Cd in the water sample was under the method detection limit (< 0.0039 mg/L), the levels of Cu, and Zn were found to be under the respective permitted limits. However, the level of lead throughout the sampling sites ranged from 0.064 to 0.108, which is 6 to 10 times higher than the permitted level in drinking water confirming the awkwardness of using the lake water for drinking. A detailed study of the catchment on the possible sources of pollution is recommended so that appropriate control measures could be taken by the governmental bodies.